(3QSGdI aj EKHGJ hGLH GdhLhOs - (3eLghds
(3ChdgG (B:s
(3HYO GdHSedI ; GYde Cf eMUd GdJhMjO EKHGJ hLhO aQO hGMO ddhGLH hGeJfGY aQO BNQ efg hdPG GhQOhG cdeI dG Edg EdG Gddg Cf NHQ dG GdebOQ ajgG ZeG ehLhO Gh eecf aYdi GdChd EfeG JOd GdcdeI GdWjHI Ydi YOe aQO BNQ dG Ydi GeJfGYg s
(3BNQgG (B:s
(3hXghQ Pdc Ydi cGaI GdSGeYjf eeG dG jMJGL Edjg ddMce HESdGege Hd XghQg YfO GdTGQY cGf hdYd ajg JfHjgG Ydi Gf GdYhGe djShG ecdajf HGdYde HJaGUjd hCjVG ajg ETGQI Edi Cf eG bGd Gddg JHGQc dG jcda Gddg faSG EdG hSYgG hEdi eG bGd GdfHj Udi Gddg Ydjg hSdes
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3GdJhMjO hGdedd hGdfMds